Patterns of Sexually Transmitted Co-infections and Associated Factors Among Men Who Have Sex With Men: A Cross-Sectional Study in Shenyang, China - Ye, Ze-Hao; Chen, Shuo; Liu, Fan; Cui, Si-Tong; Liu, Zhao-Zhen; Jiang, Yong-Jun; Hu, Qing-Hai (Frontiers in Public Health, 2022)
Background Men who have sex with men (MSM) are disproportionately affected by sexually transmitted infections (STIs). We sought to describe patterns of sexually transmitted co-infections and explore factors associated with increased acquisition of STIs among MSM. Methods We enrolled MSM in Shenyang, China, between July and December 2020 to test for four STIs, including human papillomavirus (HPV), Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Treponema pallidum (TP). Data regarding demographic and behavioral characteristics of participants were collected through a self-administered digital questionnaire. We adopted the ordinal logistic regression model to identify factors associated with acquiring more STIs. Results Overall, 177 participants with completed test results for all four STIs were analyzed. These participants had a median age of 29.0 (interquartile range: 23.0–38.0) years. The prevalence of STI co-infections was 23.7% [42/177; 95% confidence interval (CI), 17.8%−30.8%], among which HPV/CT (47.1%) and HPV/CT/NG (50.0%) co-infection were the predominant types among participants with dual and multiple infections, respectively. Participants who had a higher educational background [adjusted odds ratio (aOR), 0.46; 95% CI, 0.24–0.85; P = 0.014] and had a history of STIs (aOR, 2.53; 95% CI, 1.24–5.18; P = 0.011) were positively associated with acquiring more STIs. Conclusions MSM in Shenyang suffer a substantial burden of sexually transmitted co-infections. An optimized multi-STI integration strategy targeting prevention, surveillance, screening, and treatment is warranted to reduce the prevalence of sexually transmitted co-infections, especially in less-educated MSM.